'Terror to evil-doers' : prisons and punishments in nineteenth-century Ontario - Oliver, Peter, 1939- (Osgoode Society for Canadian Legal History., 1998)
"This is the history of the foundations of modern carceral institutions in Ontario. Drawing on a wide range of previously unexplored primary material - including the papers of prison inspectors and officials and the correspondence of those who wrote to the authorities - Peter Oliver provides a narrative and interpretative account of the penal system in nineteenth-century Ontario." "'Terror to Evil-Doers' focuses on the purposes and internal management of particular institutions. By synthesizing a wealth of new material into a comprehensive framework, Oliver's seminal study lays the groundwork for future students and scholars of Canadian history, criminology, and sociology."--Jacket.